KAJIAN PENERAPAN ECOHOUSING DAN GREEN BUILDING DI PERKOTAAN - Asharsinyo, Doddy Friestya; Hanafiah, Ully Irma Maulina (FORUM BANGUNAN, 2013)
The house does not only affect us but also the environment around us either directly or indirectly. How the house looks, built and where it is built, all have an impact on our environment. In addition the hole also possesses a wider influence. At home we consume large amounts of resources, such as energy and water. Both resources are part of our daily lives. However, how it could be to abtain and use resources that could be damaging to the environment. Our daily activities also generate so much trash some of which may take years or even centuries to decompose. If burned, most of the garbage is toxic. Others are dangerous for many reasons. Many of the chemicals we use at home turned out to be toxic and have harmful effects in the long run, both for humans and the environment. We all want to feel comfortable and secure our home. We can make a house a comfortable place to live without ‘ harm the earth ’. And, more importantly, we can set an example to uor children in order to do rhe same. This is what is meant by sustainable living.